Shari’a: Legal or Religious Rule? A Reflection on Public Law and Beyond - Giulimondi, Fabrizio (PRAWO i WIĘŹ, 2026)
Globalization has inevitably brought theocratic and theocratic-constitutional models closer to European and Western constitutionalism. Recent historical events, often of a revolutionary and warlike nature, have accelerated constitutional developments, leading states populated predominantly by Muslim worshippers to enact constitutions in which elements of the Shari’a tradition coexist with elements of secular and predominantly legal culture. Scholars from different cultural traditions have thus been led to question the nature of the Shari’a: is it normative in the Western legal sense, or is it merely a set of religiously based rules? The answer is of great significance, not least in un derstanding whether Shari’a can “dialogue” with Western legal systems. Even more significant is the observation concerning certain Arab-Islamic constitutions (such as those of pre-Taliban Afghanistan, Iraq, Iran, Turkey, and North Africa), particularly the extent to which their reference to Shari’a may risk distorting the nineteenth-century function of constitutions. Indeed, a careful and rational use of comparative law, combined with historical-legal analysis, can lead to a fruitful comparison between the two major cultural areas, enriching both legal-constitutional traditions – with greater secularization in one and a deeper emphasis on ethical and value-based considerations in the other.